Physical Qualities Pertaining to Shorter and Longer Change-of-Direction Speed Test Performance in Men and Women - Robert G. Lockie; Brett K. Post; J. Jay Dawes (MDPI AG, 2019)
This study investigated relationships between shorter (505, change-of-direction (COD) deficit as a derived physical quality) and longer (Illinois agility test; IAT) COD tests with linear speed, lower-body power (multidirectional jumping), and strength in recreationally-trained individuals. Twenty-one males and 22 females (similar to collegiate club-sport and tactical athletes) were assessed in: 505 and COD deficit from each leg; IAT; 20 m sprint; vertical jump (VJ height, peak anaerobic power measured in watts (PAPw), power-to-body mass ratio); standing broad jump; lateral jump (LJ) from each leg; and absolute and relative isometric midthigh pull (IMTP) strength. Partial correlations calculated sex-determined relationships between the COD and performance tests, with regression equations calculated (p < 0.05). The 505 and IAT correlated with all tests except PAPw and absolute IMTP (r = ±0.43⁻0.71). COD deficit correlated with the LJ (r = −0.34⁻0.60). Left- and right-leg 505 was predicted by sex, 20 m sprint, and left-leg LJ (70⁻77% explained variance). Right-leg COD deficit was predicted by sex and left-leg LJ (27% explained variance). IAT was predicted by sex, 20 m sprint, right-leg LJ, and relative IMTP (84% explained variance). For individuals with limited training time, improving linear speed, and relative lower-body power and strength, could enhance shorter and longer COD performance.